QTLs and eQTLs mapping related to citrandarins' resistance to citrus gummosis disease - Lima, Rômulo P.M. [UNESP] (2018)
Background: Phytophthora nicotianae Breda de Haan (Phytophthora parasitica Dastur) causes severe damage to citrus crops worldwide. A population of citrandarins was created from the cross between the susceptible parent Citrus sunki Hort. Ex Tan. and the resistant parent Poncirus trifoliata (L.) Raf. cv. Rubidoux, both parents and two reference rootstocks (Rangpur lime and Swingle citrumelo) were grafted in a greenhouse on Rangpur lime. Inoculations were performed at 10 cm and 15 cm above the grafting region and the resulting lesions were evaluated by measuring the lesion length 60 days after inoculation. As control, non-inoculated plants of each genotype were used. In addition, we evaluated the expression of 19 candidate genes involved in citrus defense response 48 h after pathogen infection by quantitative Real-Time PCR (qPCR). We mapped genomic regions of Quantitative Trait Loci (QTLs) and Expression Quantitative Trait Loci (eQTLs) associated with resistance to P. parasitica in the linkage groups (LGs) of the previously constructed maps of C. sunki and P. trifoliata. Results: We found disease severity differences among the generated hybrids, with lesion lengths varying from 1.15 to 11.13 mm. The heritability of the character was 65%. These results indicate that there is a great possibility of success in the selection of resistant hybrids within this experiment. The analysis of gene expression profile demonstrated a great variation of responses regarding the activation of plant defense pathways, indicating that citrandarins have several defense strategies to control oomycete infection. The information of the phenotypic and gene expression data made possible to detect genomic regions associated with resistance. Three QTLs and 84 eQTLs were detected in the linkage map of P. trifoliata, while one QTL and 110 eQTLs were detected in C. sunki. Conclusions: This is the first study to use eQTLs mapping in the Phytophthora-citrus interaction. Our results from the QTLs and eQTLs mapping allow us to conclude that the resistance of some citrandarins to the infection by P. parasitica is due to a favorable combination of QTLs and eQTLs transmitted by both parents.